Effect And Application of Ionization Radiation (X-Ray) In Living organism - Adhikari, Suraj Raj (Himalayan Physics, 2013)
X-ray is electromagnetic radiation of extremely short wavelength and high frequency. X-rays show wave as well as particle-like properties. X-ray is used in wide range of application such as industry, medicine and science application. It is essential tool in modern medicine. It can result in both beneficial and dangerous biological effects. These ionizing radiations penetrate the living tissues and can destroy living cells, chromosomal aberrations and carcinogenic effect. The Himalayan Physics Vol. 3, No. 3, July 2012 Page: 89-92